Groundwater circulation in the Miechów Trough and the central part of the Carpathian Foredeep (Poland): a hydrogeological conceptual model - Dendys, Marta; Szczepański, Andrzej; Tomaszewska, Barbara (Geologos, 2018)
The Miechów Trough and the central part of the Carpathian Foredeep in southern Poland have a highly complex geological structure and numerous fault zones. These features play a significant role in hydrogeological conditions of the area. In this area drinking water, medicinal groundwater or thermal groundwater occur, so recognition of their circulations is basic for reasonable groundwater management. In this note, a hydrogeological conceptual model, created for the purpose of regional scale mathematical modelling, is presented. This conceptual model illustrates the geology of the hydrogeological system modelled, as well as hydrogeological conditions and characteristics of groundwater circulation, as determined by tectonics. Typical of the research area is the wide diversity of geological and hydrogeological conditions. The Busko-Zdrój area, a region with a long history of exploitation of medicinal groundwater, presents the best example.